Evaporation and Condensation of HFC-134a and CFC-12 in a Smooth Tube and a Micro-Fin Tube (RP-630) - Eckels, Steven J.; Pate, M.B. (My University, 1991)
Evaporation and condensation heat transfer coefficients were measured for smooth and micro-fin tubes with HFC-134a and CFC-12. Micro-fin tubes are internally enhanced tubes that are characterized by numerous small fins that spiral down the tube. For example, in this study, the micro-fin tube had 60 fins with a height of 0.2 mm and an 17° spiral angle. Heat transfer measurements were performed on 3.67 m (12 ft) long tubes with inside diameters of 8.0 mm (0.31 in). Test conditions varied from 5°C to 15°C for evaporation and 30°C to 50°C for condensation. The refrigerant mass flux was varied from 130 kg/m²·s (95,860 lb/ft²·h) to 400 kg/m²·s (294,000 lb/ft²·h). When HFC-134a was compared to CFC-12 at similar mass fluxes in smooth tubes, the evaporation and condensation heat transfer coefficients were about 40% and 25% higher, respectively. A more relevant comparison of heat transfer coefficients is at equivalent cooling (or heating) capacities. In this case, the HFC-134a heat transfer coefficients were about 10% higher than CFC-12 values for both evaporation and condensation. The micro-fin tube produced higher heat transfer coefficients and pressure drops for all conditions when compared to the smooth tube. For example, for HFC-134a, heat transfer enhancement factors (defined as the convective heat transfer coefficients for the micro-fin tube divided by the value for the smooth tube measured at similar conditions) varied from 1.5 to 2.5 during evaporation and from 1.8 to 2.5 duringcondensation. Pressure drop penalty factors (defined similarly to enhancement factors)for both refrigerants were usually less than the heat transfer enhancement factors. However, in the case of HFC-134a at the lowest temperature and highest mass flux, the penalty factor slightly exceeded the enhancement factor.
Citation: Eckels, S.J. and M.B. Pate, Evaporation and condensation of HFC-134a in a smooth tube and a micro-fin tube. ASHRAE Transactions, 1991. 97(2): p. 68-78.